2020
DOI: 10.1002/bsd2.125
|View full text |Cite
|
Sign up to set email alerts
|

Do agenda 2030 and Sustainable Development Goals act at local and operational levels? Evidence from a case study in a large energy company in Italy

Abstract: This paper investigates the relationship between the business orientation to sustainability read under the lens of viable systems, and the operational and local dimensions of the Sustainable Development Goals (SDGs). The study deals with the experience of an Italian company operating as a monopolist in the energy industry, and it focuses on three innovative power transmission lines built in the 2000s. All the construction processes are analysed in order to explore both the operational effects and local impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Other scattered works analyzed indirectly organizational engagement with SDGs through limited case-studies (e.g., Battaglia et al, 2020;Mansell et al, 2020;Vildåsen, 2018). For example, Battaglia et al (2020) analyzed the operational dimensions of the SDGs for the case of a large Italian energy company. A set of relevant works were also focused on SDG reporting to scrutinize the organizational engagement with the goals.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other scattered works analyzed indirectly organizational engagement with SDGs through limited case-studies (e.g., Battaglia et al, 2020;Mansell et al, 2020;Vildåsen, 2018). For example, Battaglia et al (2020) analyzed the operational dimensions of the SDGs for the case of a large Italian energy company. A set of relevant works were also focused on SDG reporting to scrutinize the organizational engagement with the goals.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
“…In the second group of studies, a number of recent works have focused on the organizational level to analyze the engagement with SDGs. Van Zanten and Van Tulder (2018) conducted a survey of 81 large MNCs from Europe and North America, and found that companies are more likely to engage with SDG targets relevant to their own value chain operations, and with targets that “avoid harm” rather than “do good.” Other scattered works analyzed indirectly organizational engagement with SDGs through limited case‐studies (e.g., Battaglia et al, 2020; Mansell et al, 2020; Vildåsen, 2018). For example, Battaglia et al (2020) analyzed the operational dimensions of the SDGs for the case of a large Italian energy company.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
“…Agenda for Sustainable Development, Sustainable Development Goals (SDGs) or net zero commitment requires long-term planning and commitment at the country level (Battaglia et al, 2020). While following the accomplishment of these goals, policy development and resource allocation play a fundamental role whereas SR works as a monitoring and controlling tool (Thoradeniya et al, 2022).…”
Section: Even Though Pursuing Initiatives At the Global Level Like Th...mentioning
confidence: 99%
“…Currently, digitization and paperless movement are holistic topics amongst modern societies, and these are grounded by several reasons related to environmental motives, cost reduction, new technology, or even corporate image. Several authors point to two exogenous market drivers that are pushing the paperless movement: (1) the orientation for sustainability [1,2,20]; and (2) the digitization of information as a consequence of information and communication technology (ICT) revolution [14,[21][22][23][24], creating opportunities to diffuse digital documents throughout networks [25].…”
Section: From Dematerialization To Digitization and Paperless Firms' Movementmentioning
confidence: 99%
“…What can be done to assure the future of the next generations? The environmental consequences of the continued economic growth resulted in intense academic and political debates, calling for a transition to a "green economy" and a complete change in the paradigm of growth and development, which resulted in the notions of orientation to sustainability [1,2] and dematerialization. Some authors use the notion of dematerialization as a synonym for digitization [2,3], service innovation [1,4], organizational technology [5], or servitization/deservitization [6,7].…”
Section: Introductionmentioning
confidence: 99%